Predictors of poor seroconversion and adverse events to SARS-CoV-2 mRNA BNT162b2 vaccine in cancer patients on active treatment. (December 2021) - Buttiron Webber, Tania; Provinciali, Nicoletta; Musso, Marco; Ugolini, Martina; Boitano, Monica; Clavarezza, Matteo; D'Amico, Mauro; Defferrari, Carlotta; Gozza, Alberto; Briata, Irene Maria; Magnani, Monica; Paciolla, Fortuna; et al.
Abstract: Purpose: Initial findings in patients with cancer suggest a lower seroconversion to SARS-CoV-2 vaccination possibly related to myelo-immunosuppressive therapies. We conducted a prospective study to assess factors predicting poor seroconversion and adverse events following immunisation (AEFI) to the BNT162b2 vaccine in patients on active treatment. Patients and methods: Cancer patients, candidates to two doses of BNT162b2 SARS-CoV-2 vaccination, were enrolled. Patients on active surveillance served as controls. The primary endpoint was poor seroconversion (anti S1/S2 IgG < 25 AU/mL) after 21 days from the second dose. Results: Between March and July 2021, 320 subjects were recruited, and 291 were assessable. The lack of seroconversion at 21 days from the second dose was 1.6% (95% CI, 0.4–8.7) on active surveillance, 13.9% (8.2–21.6) on chemotherapy, 11.4% (5.1–21.3) on hormone therapy, 21.7% (7.5–43.7) on targeted therapy and 4.8% (0.12–23.8) on immune-checkpoint-inhibitors (ICI). Compared to controls, the risk of no IgG response was greater for chemotherapy (p = 0.033), targeted therapy (0.005) and hormonotherapy (p = 0.051). Lymphocyte count < 1 × 10 9 /L (p = 0.04) and older age (p = 0.03) also significantly predicted poor seroconversion. Overall, 43 patients (14.8%) complained of AEFI, mostly of mild grade. Risk of AEFI was greater in females (p = 0.001) and younger patients (p = 0.009). Conclusion: Chemotherapy, targeted therapy, hormone therapy, lymphocyte count < 1 × 10 9 /L, and increasing age predict poor seroconversion after two doses of BNT162b2 in up to 20% of patients, indicating the need for a third dose and long-term serological testing in non-responders. AEFI occur much more frequently in women and younger subjects who may benefit from preventive medications. ClinicalTrials.gov Identifier: NCT04932863 . Highlights: SARS-CoV-2 infection leads to increased morbidity and mortality in cancer patients. Up to 20% of patients on treatment had poor seroconversion after two BNT162b2 doses. Lymphocyte count, age and chemo, targeted and hormone-therapy predict poor response. Adverse events following vaccine were more frequent in women, young and non-smokers. A booster dose and long-term surveillance is needed in 20% of patients on treatment.